2022
DOI: 10.3389/fmicb.2022.1046176
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A causes severe fever with thrombocytopenia syndrome virus-induced cytokine storm by regulating mitogen-activated protein kinase pathway

Abstract: IntroductionSevere fever with thrombocytopenia syndrome (SFTS) has become a global threat to public health since its first report in China in 2009. However, the pathogenesis of SFTS virus (SFTSV) in humans remains unclear. Also, there are no effective therapeutics for SFTS. Cyclophilin A (CyPA) regulates protein folding and trafficking involved in various viral infectious diseases, but its role in SFTSV infection has not been elucidated.MethodsWe detected plasma CyPA levels in 29 healthy subjects and 30 SFTS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Consistent with the in vitro experiments, AC-73 treatment attenuated the increase in xenograft tumor volume and weight induced by TIE1 overexpression (Figure 5 F-H). It has been reported that AC-73 could specifically disrupt Basigin dimerization, thereby suppressing the Basigin/ERK1/2/MMPs pathways 23 , 24 . So, we conducted a Western blotting experiment, confirming that TIE1 can activate MAPK/ERK pathway in cervical cancer cells ( Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the in vitro experiments, AC-73 treatment attenuated the increase in xenograft tumor volume and weight induced by TIE1 overexpression (Figure 5 F-H). It has been reported that AC-73 could specifically disrupt Basigin dimerization, thereby suppressing the Basigin/ERK1/2/MMPs pathways 23 , 24 . So, we conducted a Western blotting experiment, confirming that TIE1 can activate MAPK/ERK pathway in cervical cancer cells ( Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…From a histopathological standpoint, the spleen, liver, and kidney exhibit lesions upon SFTSV infection [ 44 ]. Infiltration of inflammatory cells and necrotic lesions are observed in the liver.…”
Section: Discussionmentioning
confidence: 99%